FDI as an Export-Platform: A Gravity Model for the Danish Agri-Food Industry - Luljeta Hajderllari; Kostas Karantininis; Lartey G. Lawson (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
We investigate factors affecting Foreign Direct Investment (FDI) outflow from Danish agri-food firms to the rest of the world. We develop a conceptual model and subsequently use a gravity model based on data from 127 countries receiving Danish FDI in agri-food in 2004-2008. We find higher Danish FDI towards countries with large exports of agri-food, thereby supporting the hypothesis that FDI is used as an export-platform. FDI is coupled with high exports from Denmark, probably of raw or semi-processed food products for further processing and exports. We also find that FDI is higher in countries with stable political regimes.
Keywords: F14; F23; Q17; Q13; 330; FDI; export-platform; Danish Agri-Food; gravity model